Some physiological and biochemical responses to copper of detached cucumber (Cucumis sativus L.) cotyledons pre-floated in salicylic acid - Çanakci-Gülengül, Songül; Yildiz, Tuğba; Deveci, Didem (Pakistan Botanical Society, 2017)
Salicylic acid (SA) is a growth regulator that promotes growth of plants under stress and non-stress conditions. In the present investigation we studied the role of salicylic acid in copper induced physiological and biochemical changes and the possible induction of oxidative stress in detached cucumber cotyledons. Detached cotyledons of young cucumber seedlings were floated in 150 ppm SA. Then, the responses of these cotyledons to different concentrations (0, 10, 20 ve 50 mM) of copper (CuCl2. H2O) were investigated. In detached cucumber cotyledons exposed to increasing Cu concentrations, the fresh weight accumulation and the photosynthetic pigment content were decreased. Furthermore, the levels of some important parameters regarding oxidative stress in the cotyledons, namely lipid peroxidation (MDA), glutathione (GSH) and proline were increased. In the detached cucumber cotyledons pre-floation process with SA alleviated the negative effect of Cu (20 mM and 50 mM Cu) on growth parameters. © 2017, Pakistan Botanical Society. All rights reserved.
Keywords: Copper; Cotyledon; Cucumber; SA; Toxic effect